Estudo da influência da solidificação unidirecional em regime transiente de fluxo de calor na macro e microestrutura de ligas dos sistemas Al-Ni E Al-Cu-Ni - PINTO, Marlon Borges (2023)
Aluminum is the most consumed non-ferrous metal in the world, due to its excellent properties of low density, high strength, good compliance. However, it has low mechanical strength making it a limiting factor for its applications, therefore, this study seeks to study the characteristics of Al-Ni and Al-Cu-Ni alloys in order to improve the mechanical properties of aluminum alloys, aiming at their applicability in industry. Metallic alloys change with the amount of elements present in the alloy and with their interaction with other elements, and also by the manufacturing process and cooling method with changes in its structure. Any metal part, at some point before its final application, goes through the solidification process. This work was carried out from the study of alloys of the Al-Cu-Ni and Al-Ni systems, solidified in an ascending unidirectional solidification device, that is,it allows an environment conducive to heat extraction in a single direction. Directional solidification was analyzed with transient heat flux and ascending solidification, metallographic analyzes of the alloys, macrostructure and microstructure were performed with measurement of secondary interdendritic spacing, scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS), hardness tests were carried out correlating them with the secondary interdendritic spacing. Regarding the results observed in the metallographic analyzes of vertically directed grains and dendritic microstructure, it was also found that in regions closer to the heat extractor interface, the microstructure is more refined, as it has a direct relationship, according to the literature, with the cooling rate that occurs in higher values precisely in this region. Furthermore, the hardness of materials varies with increasing dendritic spacing, that is, spacing is inversely proportional to hardness. The strength of the AlCuNi ternary system alloy showed greater resistance than the AlNi binary system, with approximately 300 HB in the R1 region, while the Al-Ni alloys showed hardness in the range of 90 HB and 190 HB, respectively, Al-2, 5%Ni and Al-9%Ni.